Penguatan Literasi Moderasi Beragama Bagi Guru Agama Sekolah Dasar Di Kelurahan Perkamil Kecamatan Paal Dua Kota Manado (Pendekatan Participatory Action Research) - Taufik, Taufik; Rajafi, Ahmad; Lasido, Nur Allan; Ilmudinulloh, Rafiud Ilmudinulloh; Ilham, Abrari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) IAIN Manado, 2024)
Religious teachers have a key role in instilling religious moderation in the younger generation. Through their experiential approach and capacity to teach moderation values, Religious Teachers are expected to be role models of ethics and morality. They also need to open up correct and valid information, making them a source of information that can form a moderate, tolerant and harmonious society. The community service program was conducted in Perkamil Village, Manado, with a focus on Elementary School Religious Teachers. Using a Participatory Action Research (PAR) approach, the program includes mapping of religious issues, teacher training, and development of religious moderation literacy. The mapping results identified incomprehension, inequality, lack of interfaith dialog, identity politics, lack of multicultural education, and irresponsible media as the main problems. Strengthening religious moderation literacy is done through curriculum alignment, teacher training, collaborative learning activities, and mastering multicultural issues. These steps are expected to create functional and sustainable institutions and communities, and accelerate the implementation of religious moderation in elementary schools. Through these efforts, the community is expected to overcome potential religious conflicts and build an inclusive environment. Keywords: Religious Moderation, Religious Teachers, Participatory Action Research, Perkamil